2015
DOI: 10.1038/srep18193
|View full text |Cite
|
Sign up to set email alerts
|

RNA-mediated paternal heredity of diet-induced obesity and metabolic disorders

Abstract: The paternal heredity of obesity and diabetes induced by a high-fat and/or high-sugar diet (Western-like diet) has been demonstrated through epidemiological analysis of human cohorts and experimental analysis, but the nature of the hereditary vector inducing this newly acquired phenotype is not yet well defined. Here, we show that microinjection of either testis or sperm RNA of male mice fed a Western-like diet into naive one-cell embryos leads to the establishment of the Western-like diet-induced metabolic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
288
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(309 citation statements)
references
References 40 publications
18
288
2
1
Order By: Relevance
“…In the new paper published in Science, they used hepatic Squalene epoxidase (Sqle) expression in offspring resulting from IVF as a read-out for successful transmission of a phenotype. Consistent with a previous study [5], they report altered miRNA levels in sperm of males subjected to altered diet, but subsequently focused on tRNA fragments [7] which they found to be the most abundant class of RNA in mature sperm and therefore in their opinion have the highest chance to be functionally relevant in the zygote after fertilization.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In the new paper published in Science, they used hepatic Squalene epoxidase (Sqle) expression in offspring resulting from IVF as a read-out for successful transmission of a phenotype. Consistent with a previous study [5], they report altered miRNA levels in sperm of males subjected to altered diet, but subsequently focused on tRNA fragments [7] which they found to be the most abundant class of RNA in mature sperm and therefore in their opinion have the highest chance to be functionally relevant in the zygote after fertilization.…”
supporting
confidence: 78%
“…To establish a connection between tRF-mediated regulation of gene expression in the embryo and the specifically gained tRFs during sperm transit through the epididymis, they report decreased MERVL target expression in zygotes generated by IVF with cauda sperm as compared to testicular sperm. Sharma et al [7] interpret that solely sperm tRFs gained during spermatogenesis enable full elicitation of expression changes in offspring, while the study from Grandjean et al [5] shows the induction of a full metabolic phenotype after total testis RNA injection. Obvious next steps should involve the investigation of the biological consequences of altered MERVL target expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, in a subsequent study, these 339 authors reported that inserting only these nine miRNAs into normal zygotes was sufficient to induce 340 the same phenotype indicative of paternal stress (Rodgers et al 2015). Similarly, it has been reported 341 that injection of candidate miRNAs into normal zygotes recapitulates hereditary metabolic syndrome 342 associated with paternal obesity (Grandjean et al 2015). Thus, taken together, the evidence provides a 343 strong case for miRNAs as a principal language of environmental inheritance.…”
Section: Dysregulation 292mentioning
confidence: 87%
“…These are scarce in testicular sperm but acquired as sperm mature in the epididymis after fusion with epididymosomes (Sharma et al 2015). Furthermore, mice fed with western-like diet (high-fat or high-sugar) presented with altered sperm microRNA profiles, and the subsequent transfer of altered microRNAs through ICSI led to the establishment of western-like-dietinduced metabolic phenotype in offspring (Grandjean et al 2015).…”
Section: Journal Of Endocrinologymentioning
confidence: 99%